2021
DOI: 10.1038/s41565-021-00915-2
|View full text |Cite
|
Sign up to set email alerts
|

Foldamer-based ultrapermeable and highly selective artificial water channels that exclude protons

Abstract: The outstanding capacity of aquaporins (AQPs) for mediating highly selective superfast water transport 1-7 has inspired recent development of supramolecular monovalent ion-excluding artificial water channels (AWCs). AWC-based bioinspired membranes are proposed for desalination, water purification, and other separations applications [8][9][10][11][12][13][14][15][16][17][18] . While some recent progress has been made in synthesizing AWCs that approach the water permeability and ion selectivity of AQPs, a hallma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
70
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(70 citation statements)
references
References 71 publications
0
70
0
Order By: Relevance
“…Interestingly, a variety of artificial water channels have been reported to have high unitary water permeabilities, p f , and, at the same time, high E A values for water transport. Besides narrow sub-8-Å CNTs (Tunuguntla et al 2017 ; Li et al 2020 ), aquafoldamers (Shen et al 2020 ; Roy et al 2021 ) provide an additional example. At first glance, the combination of high p f and high E A appears odd because a steeply uphill pathway is seldom a fast one.…”
Section: Single-file Water Transport and Selectivity In Artificial Channelsmentioning
confidence: 99%
“…Interestingly, a variety of artificial water channels have been reported to have high unitary water permeabilities, p f , and, at the same time, high E A values for water transport. Besides narrow sub-8-Å CNTs (Tunuguntla et al 2017 ; Li et al 2020 ), aquafoldamers (Shen et al 2020 ; Roy et al 2021 ) provide an additional example. At first glance, the combination of high p f and high E A appears odd because a steeply uphill pathway is seldom a fast one.…”
Section: Single-file Water Transport and Selectivity In Artificial Channelsmentioning
confidence: 99%
“…S47), i.e., p f,NaCl / p f,sucrose ( 10 ). RC is unity when the channel does not permeate NaCl ( 13 ) and smaller than unity when the channel does not reflect NaCl ( 28 ). The calculated RC for the thinnest F12 NC 4 ( A = 0.64 nm 2 ) was 1.02, indicating a substantially perfect reflection of NaCl (Fig.…”
mentioning
confidence: 99%
“…In general, charge neutrality is requested in the permeation of salt. Hence, if its cation or anion part does not permeate, the salt is considered to be reflected ( 28 ). Although the b Cl values of F12 NC 4 and F15 NC 5 were smaller than the detection limit, F18 NC 6 exhibited Cl – -induced fluorescence decay characteristics corresponding to b Cl = 9.7 × 10 −19 cm 3 s –1 per channel.…”
mentioning
confidence: 99%
“…They also have finite ionic permeability (<6 pS) for K + but are impermeable to Na +58 . The latest study has demonstrated 2.5 times water permeability than that of AQP1 with foldamer-based artificial water channels 59 .…”
Section: De Novo Design Of Water Selective Materialsmentioning
confidence: 99%